(untitled) (Journal of the College of Education for Women, 2019)
Abstract:Thanks for people’s God who brought the great book, prays and peace forhis prophet "Mohammad" the master of missioners to all people.Allah created human being in it’s best way and give him a soul thus ,he will be a human with faith that has movement and life and the centre of hissoul is the sense which differentiate human from other animals. Thissensation generated from different senses that made the soul.God had given him a protected heart, talkative tounge and clear seeingto understand with consideration, so he will prevent himself of falling in wrongby thinking and situation that he will pass by.The significance and probability of sensation had talken our attention inQur’an . Hence , it’s considered to be our subject in this research, and to finddifferent meaning for each utterance or sensation in the great Qur’anaccording to the sources of usage whether it is a true or probable meaningand each of them might have more than twenty or less meaning.They stated that this phenomena of significant pronunaction, whichreveals differentiation and richness of the great Qur’an characteristics andmiracle in it appearance of miracle in it.The leader of this section of understanding for the words andunderstanding for the words and their meaning in AL-Qur’an was the Imam"Ali bin Abu Talib" (greet on him) through him people recognize, in more thanone way, that AL-Qur’an has many sides or different meaning for eachexpression.